2022
DOI: 10.1038/s41598-022-12719-y
|View full text |Cite
|
Sign up to set email alerts
|

A noble extended stochastic logistic model for cell proliferation with density-dependent parameters

Abstract: Cell proliferation often experiences a density-dependent intrinsic proliferation rate (IPR) and negative feedback from growth-inhibiting molecules in culture media. The lack of flexible models with explanatory parameters fails to capture such a proliferation mechanism. We propose an extended logistic growth law with the density-dependent IPR and additional negative feedback. The extended parameters of the proposed model can be interpreted as density-dependent cell-cell cooperation and negative feedback on cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Although the proliferation rate in PC cells was not accurate due to the insufficient density, 23,24 we still confirmed that LINC00960 inhibited PC cell proliferation. Notably, an association between lncRNAs and glycolysis has been reported, and lncRNAs are known to regulate the progression of multiple cancers.…”
Section: Discussionmentioning
confidence: 64%
“…Although the proliferation rate in PC cells was not accurate due to the insufficient density, 23,24 we still confirmed that LINC00960 inhibited PC cell proliferation. Notably, an association between lncRNAs and glycolysis has been reported, and lncRNAs are known to regulate the progression of multiple cancers.…”
Section: Discussionmentioning
confidence: 64%